The impact of heme oxygenase-2 on pharmacological research: A bibliometric analysis and beyond - Mancuso, Cesare (Frontiers in Pharmacology, 2023)
Heme oxygenase (HO)-2 is an enzyme mainly involved in the physiologic turnover of heme and the intracellular gas sensing, very abundant in the brain, testes and vessels. Since 1990, when HO-2 was discovered, the scientific community has underestimated the role of this protein in health and disease, as attested by the small amount of articles published and citations received. One of the reason that have contributed to the lack of interest in HO-2 was the difficulty in upregulating or inhibiting this enzyme. However, over the last 10 years, novel HO-2 agonists and antagonists have been synthesized, and the availability of these pharmacological tools should increase the appeal of HO-2 as drug target. In particular, these agonists and antagonists could help explain some controversial aspects, such as the neuroprotective versus neurotoxic roles of HO-2 in cerebrovascular diseases. Furthermore, the discovery of HO-2 genetic variants and their involvement in Parkinson’s disease, in particular in males, opens new avenues for pharmacogenetic studies in gender medicine.